HUBUNGAN DERAJAT DIFERENSIASI DENGAN JUMLAH SEL RADANG LIMFOSIT PADA HISTOPATOLOGI KANKER KOLOREKTAL - Wahyuni, Dina; Wibowo, Agung Ary; Oktaviyanti, Ika Kustiyah; Budiwinata, Winardi; Rosida, Lena (Universitas Lambung Mangkurat, 2023)
Colorectal cancer is the third most common cause of death in the world. Colorectal cancer was ranked third in Indonesia. Colorectal cancer patients had a statistically significant difference in lymphocyte inflammatory cell values compared to healthy controls. Colorectal cancer patients had much higher lymphocyte inflammatory cell values than healthy controls. Lymphocyte infiltration can provide additional prognostic information for treatment options in some situations. Histopathology is an essential factor in determining the diagnosis, treatment management, and prognosis. Histopathological examination of the degree of differentiation can determine whether a neoplasm is malignant. The prognosis of colorectal cancer depends on the presence or absence of metastases and the degree of differentiation; with a histopathological examination, we can see the spread of inflammatory cell infiltration at the degree of differentiation which can be used to determine the prognosis of colorectal cancer. The normality test results of the p-value of inflammatory lymphocyte cells were <0.001. Correlation data analysis using the rank-spearman test showed p>0.05 in colorectal cancer patients at Ulin Hospital Banjarmasin.